PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER DAN EARNING PER SHARE TERHADAP HARGA SAHAM - Kalifatullah, Sir (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2018)
This research aimed to determine: the influence of Current Ratio to cost of share; the influence of Debt to Equity Ratio to cost of share; the influence of Total Assets Turnover to cost of share; the influence of Earning Per Share to cost of share; the influence of Current Ratio, Debt to Equity ratio, Total Assets Turnover and Earning Per Share to cost of share in customer goods industry company listed in Indonesian Stock Exchange 2015. This research types was descriptive and asosiative causal. Population of this research was annual report audited and closing cost of share in customer goods industry company listed in Indonesian Stock Exchange 2015.The samples consisted of 31 companies witch were selected by using purposive sampling technique. The analysis technique used simple regression analysis and multiple regression analysis. The results of this study were: Current Ratio, Debt to Equity Ratio, and Earning Per Share didn’t have influence to cost of share, only Total Assets Turnover have influence to cost of share with regression model Cost of Share = - 13.132 + 17.809 TATO. Simultaneously, Current Ratio, Debt to Equity Ratio, Total Assets Turnover and Earning Per Share in customer goods industry had influence to cost of share with regression model Cost of Share = - 22.339 + 2.523 CR – 1.483 DER + 19.211 TATO + 1,03 EPS.